Anti-Restriction Protein, KlcAHS, Promotes Dissemination of Carbapenem Resistance - Liang, Wei; Xie, Yingzhou; Xiong, Wei; Tang, Yu; Li, Gang; Jiang, Xiaofei; Lu, Yuan (Frontiers in Cellular and Infection Microbiology, 2017)
Carbapenemase-producing Klebsiella pneumoniae (KPC) has emerged and spread throughout the world. A retrospective analysis was performed on carbapenem-resistant K. pneumoniae isolated at our teaching hospital during the period 2009-2010, when the initial outbreak occurred. To determine the mechanism(s) that underlies the increased infectivity exhibited by KPC, Multilocus Sequence Typing (MLST) was conducted. A series of plasmids was also extracted, sequenced and analyzed. Concurrently, the complete sequences of blaKPC-2-harboring plasmids deposited in GenBank were summarized and aligned. The blaKPC-2 and KlcAHS genes in the carbapenem-resistant K. pneumoniae isolates were examined. E. coli strains, carrying different Type I Restriction and Modification (RM) systems, were selected to study the interaction between RM systems, anti-RM systems and horizontal gene transfer (HGT). The ST11 clone predominated among 102 carbapenem-resistant K. pneumoniae isolates, all harbored the blaKPC-2 gene; 98% contained the KlcAHS gene. KlcAHS was one of the core genes in the backbone region of most blaKPC-2 carrying plasmids. Type I RM systems in the host bacteria reduced the rate of pHS10842 plasmid transformation by 30- to 40-fold. Presence of the anti-restriction protein, KlcAHS, on the other hand, increased transformation efficiency by 3- to 6-fold. These results indicate that RM systems can significantly restrict HGT. In contrast, KlcAHS can disrupt the RM systems and promote HGT by transformation. These findings suggest that the anti-restriction protein, KlcAHS, represents a novel mechanism that facilitates the increased transfer of blaKPC-2- and KlcAHS-carrying plasmids among K. pneumoniae strains.